Participatory Notes and Stock Market Resurrection: An Appraisal - Raul, R. K. (Indian Journal of Finance, 2009)
Participatory Notes are offshore derivative Instruments issued against the underlying securities; mainly shares, stock/stock index derivatives, by the FIIs and their sub-accounts registered with SEBI, to the overseas investors; foreign funds or hedge funds who wish to invest in the ISM without registering themselves in India. They enable investors to deploy money in the country anonymously and received dividends, capital gain from Indian companies without holding shares directly. These are special type of financial instruments issued to only foreign entities other than Indian nationals, person of Indian origin or restricted entities, subject to compliance with 'know your clients (KYC)' requirements issued by the SEBI. The RBI along with several expert committees was in opinion of prohibiting FIIs to issue PNs due to its opaque nature. The SEBI, however, since October 2007 announced restriction on issuance of PNs and at the same time eased the registration norms for FIIs.